Rare as hen’s teeth: laparoscopic management of primary pelvic hydatid cyst - Gupta, Kopal; Sharma, Dron (International Journal of Advances in Medicine, 2022)
Hydatid disease is a zoonotic parasitic disease most frequently caused by echinococcus granulose Primary peritoneal hydatidosis is very rare. We report a case of primary hydatid disease of the intraperitoneal pelvic space. A 22-year-old male patient presented with a history of abdominal pain since 5 months. Abdominal examination revealed a smooth, firm, mildly tender, non-mobile lump in suprapubic region, on digital rectal examination, a smooth spherical mass was felt anteriorly and laterally outside the rectal wall, rectal mucosa was normal. All routine investigations including liver function tests were within normal limits Computed tomography scan of the whole abdomen showed giant cyst of 10×10 cm with multiple well-defined cysts in rectovesical pouch. Diagnostic laparoscopy was performed. The liver, spleen, mesentery, omentum was found to be normal. A large tense hydatid cyst was noted in the pelvic cavity. Partial peri-cystectomy with endo-cystectomy was performed. Postoperative period was uneventful and patient was discharged on 4th postoperative day. Primary intra-abdominal but extra-peritoneal localization has been reported in only 0.2-2% cases making it a very rare entity. The treatment of choice for pelvic hydatid cyst is principally a careful surgical excision. Here with minimum invasive technique this case was operated and results were excellent.